2016
DOI: 10.7150/ijms.15214
|View full text |Cite
|
Sign up to set email alerts
|

Gender Related Survival Differences in ST-Elevation Myocardial Infarction Patients Treated with Primary PCI

Abstract: Background: Data about gender as an independent risk factor for death in ST-elevation myocardial infarction (STEMI) patients is still contrasting. Aim was to assess how gender influences in-hospital and long-term all-cause mortality in STEMI patients with primary percutaneous coronary intervention (PCI) in our region.Methods: We analysed data from 2069 STEMI patients undergoing primary PCI in our institution from January 2009-December 2014, of whom 28.9% were women. In-hospital and long-term mortality were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
0
14
0
9
Order By: Relevance
“…The 24 studies (n = 430,914) [ 5 , 10 , 12 , 14 , 18 , 19 , 21 , 22 , 24 28 , 30 , 32 , 35 , 37 , 39 , 40 , 41 , 43 , 44 , 51 , 52 ] reported on PCI postoperative in-hospital mortality, which show that the in-hospital mortality of male patients was significantly lower than that of females (OR 0.58, 95% CI 0.52–0.63, P < .001, I 2 = 66%) (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 24 studies (n = 430,914) [ 5 , 10 , 12 , 14 , 18 , 19 , 21 , 22 , 24 28 , 30 , 32 , 35 , 37 , 39 , 40 , 41 , 43 , 44 , 51 , 52 ] reported on PCI postoperative in-hospital mortality, which show that the in-hospital mortality of male patients was significantly lower than that of females (OR 0.58, 95% CI 0.52–0.63, P < .001, I 2 = 66%) (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). This gender differences also reflect in 30-day mortality [OR 0.64, 95% CI 0.61–0.66, P = .04, I 2 = 40%; 19 studies (n = 523,304)], [ 2 4 , 7 , 8 , 13 17 , 23 , 25 , 26 , 33 36 , 42 , 53 ] 1-year mortality [OR 0.67, 95% CI 0.60–0.75, P < .001, I 2 = 73%; 20 studies (n = 590,590)] [ 8 , 10 , 13 , 15 17 , 20 , 25 , 26 , 28 , 30 , 33 , 35 , 36 , 38 , 43 , 44 , 53 55 ] and >2-years mortality [OR 0.71, 95% CI 0.63–0.79, P = .005, I 2 = 57%; 14 studies (n = 43,096)] [ 4 6 , 18 , 19 , 23 , 29 , 31 , 34 , 36 , 40 , 43 , 52 , 56 ] (Figs. 2 – 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies have reported a higher unadjusted women’s long-term mortality in AMI patients, whether they were ST-elevation MI patients undergoing PCI or non-ST-elevation MI patients. 2024 However, no gender differences in mortality persisted after adjustment in all except one study, where the difference persisted only in patients younger than 65 years. 22 In the present study, the female stable post-MI patients were older, had more comorbidities such as diabetes, hypertension, prior stroke, atrial fibrillation, CAD, and CKD, but were less invasively treated during the index MI, as compared with the male population.…”
Section: Discussionmentioning
confidence: 91%
“…Hal ini dikaitkan dengan perempuan cenderung memiliki gejala atipikal sehingga mereka mungkin kurang untuk mencari perawatan ke rumah sakit dan kurang mendapat pengobatan yang optimal. 15,16 Selain itu, pasien perempuan yang menjalani IKP sering berusia lebih tua dan memiliki lebih banyak komorbid. 14 Penelitian ini tidak menemukan adanya perbedaan yang bermakna antara riwayat hipertensi (p=0,462) dan riwayat diabetes melitus (p=0,453) dengan KKM.…”
Section: Pembahasanunclassified